Resistance of sugarcane cultivars to Mahanarva fimbriolata - Dinardo-Miranda, Leila Luci; Fracasso, Juliano Vilela; Perecin, Dilermando [UNESP]; Miranda, Isabella Dinardo; Rechia, Nadia Mandello; Santos Buzzatto, Driele Francine dos (Inst Agronomico, 2018)
The spittlebug Mohanarva filmbriofolato (Stal)(Hemiptera: Cercopidael is one of the roost important pest of sugarcane in Brazil, Population control measures are currently restricted to the use of chemical insecticides and the fungus Metorhizurn rqsopilue, in part because very little information exists regarding the resistance of sugarcane cultivars, Therefore, the aim of this study was to evaluate the resistance mechanisms of 18 sugarcane cultivars to AT fimbrOloto to provide in formation for growers hoping to manage this pest, Isolated buds of each cultivar were planted in pots and maintained in a greenhouse for approximately three months. The pots were then moved to climate-controlled chambers (26 +/- 1 degrees C; 70 10% RH, 12 h photoperiod) to carry out laboratory tests to evaluate adult feeding and female oviposition preferences (using both free-choice and no-choice tests) as well as the effects of the cultivars on nymph development and the cultivars tolerance to the pest attack, The least attractive cultivar for adult feeding and oviposition in free-choice test was P13867515, which was also one of those that received the fewest eggs in the no-choice oviposition tests. Cultivar CTC9 showed the highest level of antibiosis resistance, with a root nymph survival rate of 52.5%, Finally, cultivar 00966928 was the most tolerant to fimbriolata, but it showed 19% reduction in aboveground biomass weight due to the pest.
Keywords: spittlebug; antixenosis; antibiosis; tolerance